Kontribusi Usaha Gula Aren Terhadap Pendapatan Keluarga di Desa Wanga Kecamatan Motoling Timur - Kessek, Syalomitha Gratcia; Jocom, Sherly Gladys; Tarore, Melissa Lady Gisela (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2025)
This research aims to calculate the contribution of the palm sugar business to family income in Wanga Village, East Motoling District. This research uses descriptive quantitative methods. The data collected is primary data and secondary data. Primary data was collected through direct interviews with palm sugar processors using a list of questions such as a questionnaire. Meanwhile, secondary data was obtained from data related to this research taken from the village office. The research results show that the contribution of the palm sugar business to family income in Wanga Village, East Motoling District is 66.52%. This shows that the palm sugar business has a very important role in supporting the family economy in Wanga Village, with more than half of the family's income coming from the palm sugar business.